Invertendo a aula de história: sequências didáticas com propostas de ensino híbrido utilizando o Google sala de aula para turmas do ensino médio - Nascimento, Adilson Nobre do (2020)
In order to serve one of the purposes of the professional master's degree in History teaching, which is the construction of didactic material that establishes the dialogue between the classroom and the research field of History teaching, this research discusses the use of methodologies of hybrid teaching and of the classroom inverted in the school History in the scope of the high school having in Google Classroom an instrument of pedagogical mediation. Therefore, it is necessary to reflect on the applicability of this methodology in the teaching of History. Analyze the use of the inverted classroom in the teaching of History, checking the educational potential of Google Classroom for the teaching of History and finally build a textbook and analyze its application in the classroom. Then, an action research is carried out where the didactic sequences contained in the didactic manual are applied in the classes in which the teacher-researcher teaches. Therefore, as a final product of this dissertation, the didactic manual was reformulated from the observations do in its application and will be available as pedagogical support for History teachers of basic education.